Training on Making Seaweed Dodol as A Diversification of Seafood Products for the Amerta Segara Tanjung Benoa Group: Pelatihan Pembuatan Dodol Rumput Laut sebagai Diversifikasi Olahan Hasil Laut Kelompok Amertha Segara Tanjung Benoa - Puspaningrum, Dylla Hanggaeni Dyah; Sumadewi, Ni Luh Utari; Suryantari, Eka Putri (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
The Amertha Segara group as a partner that has been developing shredded tuna fish products, wants to develop other processed products. Processing seaweed into a product can be developed as a form of diversification of processed seafood in addition to fish-based products. The problem for partners is that they do not have knowledge of how to process seaweed, which is often found in the Tanjung Benoa area, into seaweed dodol. Through community service activities, training in making seaweed dodol was carried out, it is hoped that understanding and skills in producing seaweed dodol products can develop and partners can independently carry out dodol production activities. In addition, assistance in choosing packaging and designing labels was also carried out so that the products produced are suitable for wider marketing and have a competitive selling value. The results of the training obtained the level of understanding and knowledge of partners increased to 85%, and had attractive packaging and labels so that it could increase the selling value of seaweed dodol products. AbstrakKelompok Amertha Segara sebagai mitra yang selama ini mengembangkan produk abon ikan tuna, menginginkan adanya pengembangan produk olahan lainnya. Pengolahan rumput laut menjadi suatu produk dapat dikembangkan sebagai bentuk diversifikasi olahan hasil laut selain produk berbahan dasar ikan. Permasalahan bagi mitra yaitu belum memiliki pengetahuan tentang cara mengolah rumput laut yang sering dijumpai di wilayah Tanjung Benoa untuk dijadikan dodol rumput laut. Melalui kegiatan pengabdian, dilakukan pelatihan pembuatan dodol rumput laut, diharapkan pemahaman dan keterampilan dalam menghasilkan produk dodol rumput laut dapat berkembang dan mitra secara mandiri dapat melakukan kegiatan produksi dodol. Selain itu pendampingan memilih kemasan dan mendesain label juga dilakukan agar produk yang dihasilkan layak untuk dipasarkan lebih luas dan memiliki nilai jual yang kompetitif. Hasil pelatihan yang dilakukan diperoleh tingkat pemahaman dan pengetahuan mitra meningkat mencapai 85%, dan memiliki kemasan dan label yang menarik sehingga dapat meningkatkan nilai jual produk dodol rumput laut.